CARBOHYDRATE METABOLISM CONDITION IN PREMENOPAUSAL WOMEN WITH ENDOMETRIAL HYPERPLASIA - Borisov, M.V.; Kvashenko, V.P. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
It was performed an investigation of carbohydrate metabolism in patients with endometrial hyperplasia.It was proved the presence of insulin resistancy in the majority of patients. The obtained data demonstrates the nesessity of glucose tolerance test performing in order to improve hyperplasia treatment.